MUC1 modulates gastric epithelial immune response to bacteria or inflammatory stimuli - Shofyatul Y. Triyana; Yong H. Sheng; Michael McGuckin (Faculty of Medicine, Universitas Trisakti, 2012)
BACKGROUND Cell surface mucin glycoproteins are expressed on the mucosal surface. One of these cell surface mucins is mucin-1 (MUC1), which plays a role as a physical barrier and limits inflammation. However, its functional role in modulating responses to pathogens, particularly with respect to intracellular signaling, needs to be investigated. Therefore, the aim of this study was to characterize the modulation of responses of human gastric epithelial cells by MUC1 to common mucosal pathogens and inflammatory stimuli. METHODS Human gastric epithelial cell lines (MKN7) were co-cultured with Campylobacter jejuni (C. jejuni). In order to investigate the effect of MUC1 expression on C. jejuni-induced cytokine production, MKN7 cells were transfected with 1:1 small interfering RNA (siRNA) to knock down the MUC1 gene using MUC1 targeting siRNA or non targeting siRNA as a control. The read out of the experiment was interleukin (IL)-8 concentration as a result of the inflammation process. This cytokine concentration was measured using ELISA and compared between the two groups. RESULTS This study demonstrated that by using siRNA transfection, knockdown of MUC1 expression in MKN7 human gastric epithelial cells suppressed IL-8 production at the early phase of incubation, but promoted an increase in IL-8 production at the late phase, in response to C. jejuni. CONCLUSION Knockdown of the MUC1 gene in MKN7 cells reduced IL-8 levels both in the cells with and without exposure to C. jejuni. This study provides direction for exploration of the intracelular mechanisms by which cell surface mucins modulates inflammation in the response of gastrointestinal epithelial cells to pathogens or other inflammatory stimuli.